ANALISIS BEBAN KERJA MENTAL PADA OPERATOR AIR TRAFFIC CONTROLLER (ATC) DENGAN METODE SUBJEKTIF DAN OBJEKTIF (STUDI KASUS : AIRNAV BANDAR UDARA XYZ) - Fathimahhayati, Lina Dianati (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2018)
An Air Traffic Controller (ATC) operator is required to always concentrate on monitoring navigation, radiation as well as supervising and implementing aircraft guidance. Obviously such work can lead to a mental workload on the worker. Based on these problems, it is necessary to do a research on the analysis of mental workload on the operator ATC at XYZ Airport. Measurement of mental workload can be done in two ways: subjective measurement and objective measurement. Subjective measurements of the mental workload can be done with NASA-TLX method. While the objective measurement can be done by doing the measurement physiologically such as through the heart rate. The results showed that the metal workload of ATY operator of XYZ Airport was in high category and very high base on subjective measurement. Performance level is the dominant factor causing high mental work load perceived by ATC operator. While based on the objective measurement found that the mental workload of ATC operators are in the medium category.